Lamb survivability: a new approach to an old problem - Wilson, Carrie S.; Cherry, Natalie L.; Taylor, J. Bret (Frontiers in Animal Science, 2025)
Lamb survivability is an important trait from both an economic and animal welfare perspective. Five breeds at the U.S. Sheep Experiment Station were evaluated for survival to weaning and included 74,448 records from 43 years. Objectives were to evaluate 1) the influence of lamb and littermate competition on lamb survivability to 3 d and 120 d (weaning); 2) the influence of within-litter competition on birth weight; 3) the relationship between within-litter birth weight deviation and lamb survivability, 4) the influence of ewe age on lamb survivability and birth weight, and 5) reasons for and timing of lamb loss. Sex of littermate(s) had an impact on lamb survivability, which was more pronounced for triplets than for twins. Although not significant, female birth weights were lighter in mixed-sex litters than all-female litters. Within-litter birth weight deviation had an impact on lamb survivability with lambs from below mean weight litters that were more than 1 kg lighter than the litter having less than a 50% chance of survival. Both young and old ewes had lower lamb survival than mid-age ewes. Reasons for lamb loss differed depending on the age of the lamb with weak and trauma categories resulting in early loss and predation resulting in later loss. This study provides insight into within-litter competition for use in future genetic evaluation.